117 THE ASSOCIATION BETWEEN SELF-REPORTED SENSORY FUNCTION (VISION AND HEARING) AND COGNITIVE FUNCTION FROM THE IRISH LONGITUDINAL STUDY ON AGEING (TILDA). (25th October 2022) - O'Leary, E
Abstract: Background: With an aging population worldwide and in Ireland, comes more age-related health problems, including problems with hearing and vision. Ageing is also associated with a gradual decline in some cognitive functions. Sensory impairments (both hearing and vision) have been shown to have an association with cognitive impairment, with a greater cognitive decline seen in those with a combined hearing and vision loss. There is a well-established association between sensory and cognitive impairment, however, no study to date has looked at similar data collected in Ireland. The objective of this study is to analyse data from an Irish sample. Methods: This study used data collected from Wave 4 of the Irish Longitudinal Study on Ageing (TILDA). Participants with missing data or information were excluded, leaving a complete dataset of 4, 612, for analysis. Multiple linear regression analyses were carried out to compare Mini-Mental State Examination (MMSE) scores to self-reported sensory impairment (hearing impairment alone, vision impairment alone and Dual Sensory Impairment (DSI)) while adjusting for several covariates (age, gender, level of education, alcohol consumption, smoking history, depressive symptoms, mobility, loneliness, and physical activity). Results: Self-reported fair/poor hearing and self-reported fair/poor vision had statistically significant lower MMSE scores than participants with self-reported excellent/very good/good hearing and self-reported excellent/very good/good vision respectively (hearing estimated standard error: –0.055, p value: 3.67e-11; vision estimated standard error: –0.080, p value: 5.14e-15). Self-reported DSI was associated with lower MMSE scores compared to participants without DSI (DSI estimated standard error: –0.13, p value: 5.55e-13). Conclusion: This cross-sectional study and secondary data analysis demonstrated that in older Irish adults there is an association between hearing impairment, vision impairment and dual sensory impairment and lower cognitive function. These findings contribute to the growing body of research done internationally using other large scale health surveys.